2019
DOI: 10.1128/jb.00154-19
|View full text |Cite
|
Sign up to set email alerts
|

Guanine Quadruplex DNA Regulates Gamma Radiation Response of Genome Functions in the Radioresistant Bacterium Deinococcus radiodurans

Abstract: Guanine quadruplex (G4) DNA/RNA are secondary structures that regulate the various cellular processes in both eukaryotes and bacteria. Deinococcus radiodurans, a Gram-positive bacterium known for its extraordinary radioresistance, shows a genomewide occurrence of putative G4 DNA-forming motifs in its GC-rich genome. N-Methyl mesoporphyrin (NMM), a G4 DNA structure-stabilizing drug, did not affect bacterial growth under normal conditions but inhibited the postirradiation recovery of gamma-irradiated cells. Tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 61 publications
1
19
0
Order By: Relevance
“…Ding et al hypothesized that stress-resistant bacteria found in the Deinococcales may utilize putative quadruplex sequences (PQS) for gene regulatory purposes. An enrichment in prokaryote PQS has been found in thermophilic organisms [ 33 ] but also in organisms with resistance to other stress factors, such as radiation [ 36 , 37 ]; thus, a direct correlation between temperature and G4 presence is not supported by these findings. In addition, while bacteria in the Deinococcus-Thermus group are the most abundant for PQS, it is striking that the mostly thermophilic and hyperthermophilic bacteria in the Thermotogae phylum have one of the lowest PQS frequencies.…”
Section: Introductionmentioning
confidence: 99%
“…Ding et al hypothesized that stress-resistant bacteria found in the Deinococcales may utilize putative quadruplex sequences (PQS) for gene regulatory purposes. An enrichment in prokaryote PQS has been found in thermophilic organisms [ 33 ] but also in organisms with resistance to other stress factors, such as radiation [ 36 , 37 ]; thus, a direct correlation between temperature and G4 presence is not supported by these findings. In addition, while bacteria in the Deinococcus-Thermus group are the most abundant for PQS, it is striking that the mostly thermophilic and hyperthermophilic bacteria in the Thermotogae phylum have one of the lowest PQS frequencies.…”
Section: Introductionmentioning
confidence: 99%
“…322in small plasmid(Mishra et al, 2019). The change in genome copy number has also been 323 reported when the coding sequences of genome segregation proteins were deleted in this324 bacterium (Maurya et al, 2019a; Maurya et al, 2019b).…”
mentioning
confidence: 55%
“…
31Deinococcus radiodurans, an extremophile, resistant to many abiotic stresses including 32 ionizing radiation, has 2 type I topoisomerases (drTopo IA and drTopo IB) and one type II 33 topoisomerase (DNA gyrase). The role of drTopo IB in guanine quadruplex DNA (G4 DNA) 34 metabolism was shown in vitro. Here we report that D. radiodurans cells lacking drTopo IB 35 (∆topoIB) show sensitivity to G4 DNA binding drug (NMM) under normal growth conditions.
…”
mentioning
confidence: 99%
“…The cell lytic efficiency was determined using Neubauer counting chamber and the genomic DNA integrity was analysed by agarose gel electrophoresis. The genomic DNA was serially diluted and used for determining genomic copy number by quantitative Real-Time PCR as described in (Mishra et al, 2019). For standardization of qPCR two individual genes for each replicon with almost same PCR efficiency were taken for copy number determination as given in (Mishra et al, 2019).…”
Section: Determination Of Ploidy Using Quantitative Real-time Pcrmentioning
confidence: 99%